Efek Konsumsi Teh Hitam dan Jus Apel Terhadap Stabilitas Warna Laminate Veneer Resin Komposit Indirek - Modily, Nadine Grace; Syafrinani, Syafrinani (Fakultas Kedokteran Gigi Universitas Jember, 2024)
Laminate veneer is a treatment in prosthodontic that is aesthetically pleasing and requires minimal preparation that can be fabricated with indirect resin composite, which is durable and low-cost, though this material has poor color stability. Due to the increasing consumption of black tea and apple juice, there was a need for this study to be taken out. This study aims to determine the effect of consumption of black tea and apple juice on colour stability. Indirect resin composite specimens were fabricated 20 mm in diameter and 1.5 mm in thickness and divided into 3 groups (n = 10). Specimens were immersed in 3 types of solutions: black tea, apple juice and aquadest as control. The color of specimens was measured before and after immersion using a color spectrophotometer. Statistical analysis was performed with univariate test, Mann-Whitney U test, Independent T-test, one-way ANOVA and LSD test. Mean delta E (ΔE) value for black tea is 1,381 ± 0,938 and ΔE = 6,803 ± 1,757 in apple juice. Black tea and apple juice reduced the color stability of indirect resin composite significantly with p = 0,001 (p < 0.05). The effect of immersion in both drinks differed significantly with p = 0,001 (p <0.05). Apple juice experienced the greatest reduction in color stability, followed by black tea, and lastly the control group. The difference in the effect of immersing black tea and apple juice was due to the difference in pH and major acid content.